Some results on essential spectra of differential operators in Banach spaces - Erovenko, V. A. (Mathematical Modelling and Analysis, 2003)
In this paper we investigate spectral and semi‐Predholm properties of maximum and minimum Puchsian differential operators on Lebesgue spaces on a semi‐axis. These results are applied for determination of various essential spectra and spectrum of ordinary differential operators with polynomial coefficients, which order does not exceed the order of the corresponding derivative.Keletas rezultatų apie esminį spektrą Banacho erdvėseSantrauka. Šiame straipsnyje tiriamos spektrinės ir pusiau Fredholminės maksimalių ir minimalių Fuchsiano diferencialinių operatorių savybės Lebego erdvių pusiau ašyse. Šios savybės gali būti taikomos įvairiems paprastųjų diferencialinių operatorių su polinominiais koeficientais, kurių eilė neviršija atitinkamos išvestinės eilės, esminio spektro ir spektro tyrime.First Published Online: 14 Oct 2010